2019
DOI: 10.3390/polym11111746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dip Coating Polymer Solutions on Properties of Thermoplastic Cassava Starch

Abstract: Thermoplastic starch (TPS) was prepared by melt-mixing cassava starch with glycerol. Polyethylene (PE), polyethylene-grafted-maleic anhydride (PE-MAH) and poly(lactic acid) (PLA) solutions at 2% (w/v) were used to coat TPS using the dip coating process. The tensile strength of TPS increased with the dip coating solution technique, especially for PLA coating. Swelling index, water-soluble matter and water droplet contact angle confirmed the water resistant improvement of TPS by PE-MAH and the PLA dip coating so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Petroleum-based polymers generated from petroleum resources subject to depletion have detrimental effects on the environment 4 , 5 . Therefore, biodegradable polymers are being widely investigated to replace petroleum polymers, with examples including polylactic acid (PLA) 6 , 7 , polybutylene succinate (PBS) 8 , 9 , thermoplastic starch (TPS) 10 , chitosan 11 , 12 , pectin 13 – 15 , polysaccharides 16 , 17 , keratin 18 , and fibroin 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Petroleum-based polymers generated from petroleum resources subject to depletion have detrimental effects on the environment 4 , 5 . Therefore, biodegradable polymers are being widely investigated to replace petroleum polymers, with examples including polylactic acid (PLA) 6 , 7 , polybutylene succinate (PBS) 8 , 9 , thermoplastic starch (TPS) 10 , chitosan 11 , 12 , pectin 13 – 15 , polysaccharides 16 , 17 , keratin 18 , and fibroin 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous study reported that various polysaccharides were found in the peach‐shaped D. indusiata , including dulcitol, 3‐hydroxynevirapine glucuronide, gluconic acid, L‐gulonic gamma‐lactone, L‐ribulose, D‐arabinono‐1,4‐lactone, (beta‐1‐O‐[ N ‐(2‐formyl‐3‐chlorophenyl) anthraniloyl]‐D‐glucupyranu‐ronic acid) (Wang et al ., 2021). Polysaccharides from plants showed a potential not only as an active ingredient for anti‐tumour, anti‐inflammatory, immune enhancer, and a potent radical scavenger (Surin et al., 2018a; Badalyan et al ., 2019) but also used as biodegradable polymer materials, such as cassava (Jantanasakulwong et al ., 2019; Homsaard et al ., 2020; Tongdeesoontorn et al ., 2021), corn (Jantanasakulwong et al ., 2018), and rice bran (Surin et al ., 2020). Srisuk & Jirasatid (2020) reported the high concentrations of hyaluronic acid as well as allantoin had been found in the mucilage in the egg of bamboo mushroom, the latter with anti‐inflammation property.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer blending and co-polymerization are two methods that can be used to improve polymer mechanical properties [ 17 , 18 ]. Notably, PLA has been previously reported as a coating material to improve mechanical properties and water resistance of TPS [ 19 ].…”
Section: Introductionmentioning
confidence: 99%